Towards Incorporation of Blue Carbon in Falkland Islands Marine Spatial Planning: A Multi-Tiered Approach - Bax, Narissa; Barnes, David K. A.; Pineda-Metz, Santiago E. A.; Pearman, Tabitha; Diesing, Markus; Carter, Stefanie; Downey, Rachel V.; Evans, Chris D.; Brickle, Paul; Baylis, Alastair M. M.; Adler, Alyssa M.; Guest, Amy; et al. (Frontiers in Marine Science, 2022)
Ecosystem-based conservation that includes carbon sinks, alongside a linked carbon credit system, as part of a nature-based solution to combating climate change, could help reduce greenhouse gas levels and therefore the impact of their emissions. Blue carbon habitats and pathways can also facilitate biodiversity retention, aiding sustainable fisheries and island economies. However, robust blue carbon research is often limited at the scale of regional governance and management, lacking both incentives and facilitation of policy-integration. The remote and highly biodiverse coastal ecosystems and surrounding continental shelf can be used to better inform long-term ecosystem-based management in the vast South Atlantic Ocean and sub-Antarctic, to synergistically protect both unique biodiversity and inform on the magnitude of nature-based benefits they provide. Understanding key ecosystem information such as their location, extent, and condition of habitat types, will be critical in understanding carbon pathways to sequestration, threats to this, and vulnerability. This paper considers the current status of blue carbon data and information available, and what is still required before blue carbon can be used as a conservation management tool integrated in national Marine Spatial Planning (MSP) initiatives. Our research indicates that the data and information gathered has enabled baselines for a number of different blue carbon ecosystems, and indicated potential threats and vulnerability that need to be managed. However, significant knowledge gaps remain across habitats, such as salt marsh, mudflats and the mesophotic zones, which hinders meaningful progress on the ground where it is needed most.